2017
DOI: 10.16965/ijar.2017.247
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Incidence of the Carotico-Clinoid Foramen in the South Indian Dry Adult Skulls: A Cross-Sectional Study

Abstract: Introduction: Existence of the carotico-clinoid foramen causes compression of the clinoid segment of internal carotid artery and also increases the risk of hemorrhage while dealing performing various surgical procedures related to para clinoid aneurysms and tumors of this region. The present study was aimed to find out the incidence of the carotico-clinoid foramen in south Indian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…2 A racial variation has also been reported regarding CCF, which shows highest incidence in Turkish population (35-67%) followed by Japanese (9.9%) and Brazilians (2.5%). 6 In addition it was found more frequent on the right side (9.2%) than on the left (5.5%) 10 . Moreover regarding the sexual variations, reports were contradictory.…”
Section: Discussionmentioning
confidence: 92%
“…2 A racial variation has also been reported regarding CCF, which shows highest incidence in Turkish population (35-67%) followed by Japanese (9.9%) and Brazilians (2.5%). 6 In addition it was found more frequent on the right side (9.2%) than on the left (5.5%) 10 . Moreover regarding the sexual variations, reports were contradictory.…”
Section: Discussionmentioning
confidence: 92%
“…In the work of Bansode et al (2017), it was reported that, of the 35 skulls studied, only 7 (20 %) presented the CF. In these skulls, 2 (5.7 %/28.6 % -2:35/2:7) had the complete bilateral CF, 2 (5.7 %/28.6 % -2:35/2:7) complete right unilateral, 2 (5.7 %/28.6 % -2:35/2:7) incomplete, in right unilateral and 1 (2.8 %/14.3 % -1:35/1:7) incomplete left unilateral.…”
Section: Discussionmentioning
confidence: 96%
“…Freire et al studied 80 Brazillian dry skulls and detected this foramen in 6.25% of specimens [10]. Plenty of literature describes the occurrence of this foramen in the Indian population [11][12][13][14][15][16][17][18][19]. The incidence of this foramen ranges from 6% to 37% in the Indian population.…”
Section: Review Classification and Incidence Of Carotico-clinoid Foramenmentioning
confidence: 99%